P01.057 Effects of tumor treating fields on health-related quality of life (HRQoL) in newly diagnosed glioblastoma: An exploratory analysis of the EF-14 randomized phase III trial. (19th September 2018) - Walbert, T; ,; Lavy-Shahaf, G
Abstract: Background: Tumor Treating Fields (TTFields) are a novel treatment modality that continuously delivers alternating electric fields to the tumor region. TTFields interfere with the assembly of the mitotic spindle leading to apoptosis. In the EF-14 phase III study in newly diagnosed glioblastoma, TTFields plus temozolomide (TTFields/TMZ) showed significant increase in overall and 5-year survival rates compared to temozolomide. TTFields/TMZ did not negatively impact nine prespecified HRQoL scales (global health, physical, cognitive, role, social and emotional functioning, itchy skin, pain, and leg weakness) except for increased itchy skin. We present an exploratory analysis of the remaining 17 EORTC QLQ C-30 and BN-20 HRQoL scales. Material and Methods: HRQoL was measured by the EORTC QLQ-C30 and BN20 questionnaires at baseline and every 3 months thereafter. Mean changes from baseline as well as significant changes in scores over time (>10 points) were evaluated using a repeated measures test. Deterioration-free survival and time-to-deterioration in HRQoL were assessed for each scale, as well as % patients with stable/improved HRQoL versus baseline. Results: No statistically or clinically significant decline in any of the exploratory HRQoL scales was seen in the repeated measures analysis or in time to deterioration. Significantly more patients treated with TTFields/TMZ versus TMZ reported stable/improved bladder control (63.6% versus 46.8%, p=0.001) and diarrhea (60.6% versus 43.7%, p=0.001) compared to baseline. The deterioration-free survival for diarrhea, future uncertainty and headaches was significantly delayed in TTFields/TMZ treated patients compared to TMZ alone (HR 0.68, 0.71 and 0.67, respectively, p<0.001). Conclusion: No negative impact of HRQoL was seen in any of the exploratory scales between patients treated with temozolomide only or TTFields and TMZ. Adding TTFields to standard therapy in newly diagnosed glioblastoma does not appear to negatively impact QoL.